TRANSLATION PROBLEMS OF ENGLISH BORROWINGS RELATED TO THE FIELD OF EDUCATION - Boymurodova Marvaridbonu Sayfulla qizi; Supervisor, Madiyeva Madina Yusupovna (Journals Park Publishing, 2024)
This study explores the challenges of translating English borrowings in the educational field, focusing on semantic, linguistic, and cultural issues. Drawing on the perspectives of both international and Uzbek scholars, it identifies common translation errors and proposes practical strategies for improving accuracy and contextual relevance. Examples of terms like “curriculum” and “credit hours” in Uzbek educational texts illustrate these challenges.
Keywords: Curriculum, credit hours, assessment, syllabus, liberal arts education, online learning, rubrics.